2009
DOI: 10.1159/000200804
|View full text |Cite
|
Sign up to set email alerts
|

A Twelve-Year Experience with Adrenal Cortical Carcinoma in a Single Institution: Long-Term Survival after Surgical Treatment and Transcatheter Arterial Embolization

Abstract: Introduction: We retrospectively analyzed 6 cases of adrenal cortical carcinoma (ACC) treated during a 12-year period at a single institution. Patients and Methods: We reviewed the clinical and pathological records and updated the follow-up of the patients treated and observed in our institution between 1995 and 2006. Results: All 6 patients underwent surgery for ACC. The mean age at diagnosis was 53.3 years (range 36–72). The median follow-up was 50.7 months (range 13–132). Three patients were clinically clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 61 publications
0
18
0
Order By: Relevance
“…Experience with percutaneous ablation has been described as a feasible approach, with outcomes at least comparable to those of local surgical resection 11,13 . Positive short‐term results are reported with both TAE and radioembolization 29,30 . When considering IGLTs, it is important to bear in mind that transarterial therapy is more often palliative in nature, while ablation is potentially extirpative and may be curative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experience with percutaneous ablation has been described as a feasible approach, with outcomes at least comparable to those of local surgical resection 11,13 . Positive short‐term results are reported with both TAE and radioembolization 29,30 . When considering IGLTs, it is important to bear in mind that transarterial therapy is more often palliative in nature, while ablation is potentially extirpative and may be curative.…”
Section: Discussionmentioning
confidence: 99%
“…11,13 Positive short-term results are reported with both TAE and radioembolization. 29,30 When considering IGLTs, it is important to bear in mind that transarterial therapy is more often palliative in nature, while ablation is potentially extirpative and may be curative. Therefore, in situations in which the option of ablation or TACE exists, ablation may be more optimal, if a tumor-free margin by imaging can be achieved.…”
mentioning
confidence: 99%
“…TACE, localized chemoembolization, is based on a selective embolization with injection of a high intratumor levels of cytotoxic substances with a minimum of systemic effects. Predictors of response were a size of <3 cm and high lipidol uptake (Soga et al, 2009 ).…”
Section: Metastatic Accmentioning
confidence: 99%
“…Adrenal tumors are detected unexpectedly in 1% to 4% of all abdominal imaging studies, and approximately 5% of those incidentalomas are found as ACCs. 26 From Korean data, 4.3% of the 348 cases of adrenal incidentalomas were identified as ACC. 27 However, because of its rapid progression and poor prognosis, incidentally detected tumors are not restricted to a limited stage and are not associated with favorable survival.…”
Section: Discussionmentioning
confidence: 99%